Photocatalytic Efficiency of TiO2-Biomass Loaded Mixture for Wastewater Treatment - Kanakaraju, Devagi; Wong, Soon Pang (Hindawi, 2018)
The objective of this study was to assess the efficiency of a novel TiO2/modified sago bark (TiO2/MSB) mixture for the degradation of sago wastewater effluent by employing response surface methodology (RSM) using chemical oxygen demand (COD) removal as the target parameter. The highest COD removal of 64.92% was obtained using TiO2/MSB mixture sample prepared by combining 0.2 g/L TiO2 and 1 w/w% MSB. Given that the highest removal was produced using this mixture sample, further optimisation of sago wastewater treatment was conducted by varying the independent variables, namely, dosage and contact time. Under this optimum condition, 0.10 g of 0.2 g/L TiO2/1% MSB had successfully reduced 52.83% COD in 120 min. Surface morphology, functional groups, and elemental analysis supported observations of the ability of TiO2/MSB mixture to remove COD. Additionally, aeration had further improved COD removal by 11%. The regression value () of the model indicated a high degree of correlation between the evaluated parameters. These results proved the feasibility of TiO2 photocatalysis as an appealing alternative protocol for sago wastewater treatment and solid waste from the industry can be utilised for wastewater degradation.